Hydatid cysts of the pulmonary artery - YILDIZELİ, BEDRETTİN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2016)
Hydatid cyst located in the pulmonary artery is rare. The cause is usually rupture of an intracardiac cyst or dissemination from a hepatic focus either spontaneously or secondary to surgery. In this article, we report a 32-year-old patient with a history of hepatic and pulmonary hydatid cyst resection, presenting with multiple hydatid cysts located in the right pulmonary artery, and complaints of dyspnea and hemoptysis.
Keywords: Computed tomography; hydatid cyst; magnetic resonance imaging; pulmonary artery cyst; CT